THE IMPROVEMENT OF THE INTERESEST IN LEARNING SOCIAL SCIENCES USING JOYFUL LEARNING STRATEGY SUPPORTED BY FUN SOCIAL PUZZLE MEDIA - Sifa Adriani Prihatina; Sukarno Sukarno; Endang Sri Markamah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The objectives of this research are to: 1) improve the interest in Learning social sciences through the use of Joyful Learning strategy with Fun Social Puzzle media on 4th grade students 2) describe the use and the result of Joyful Learning strategy with Fun Social Puzzle media in improving the interest in Learning social science on 4th grade students. The sources of data come from researcher, teachers, and students. The data collection techniques used are: interview, observation, and interest questionnaires. The data validity test techniques used are triangulation sources and methods. Data analysis techniques used are comparative descriptive analysis and interactive analysis models. The results of this research indicate that the interest in Learning social sciences on 4th grade students using Joyful Learning strategy with Fun Social Puzzle media improves. The improvement is seen by the number of students in high interest category and very high category increase. On pre-action, students who have a high interest and very high interest on the social sciences subjects are only 32%. In cycle I it increases to 63%. In the end of the cycle II it increases to 93% or 28.